Working on distance : experience from SME-trainees working with distance spanning technology - Ylinenpää, Håkan; Lassinantti, Lars (Luleå tekniska universitet, Innovation och Design, 2001)
This paper reports on the experiences drawn from a pilot project on telecommuting, involving university trainees and smaller firms in the northernmost part of Sweden. Building on previous research in telecommuting and social integration of new co-worker into organisations, the paper addresses two main issues: (1) May utilisation of modern ICT for telecommuting be a way to overcome problems in recruiting qualified staff, and (2) what are in these cases the specific challenges prevailing for absorbing new members into an existing organisation (here a smaller firm). The results from this exploratory case study indicate support for the idea of using ICT and telecommuting as a measure to overcome recruitment problems, but also specifically pinpoint the need for both technically and socially oriented preparation and introduction. Godkänd; 2001; Bibliografisk uppgift: Publicerad i serien Arbetsrapporter, Institutionen för industriell ekonomi och samhällsvetenskap, Avd. för Industriell organisation, Luleå tekniska universitet, AR 2001:47; 20070701 (ysko)